Design and production of Al-Mn-Ce alloys with tailored properties. (15th November 2016) - Coury, F.G.; Kiminami, C.S.; Botta, W.J.; Bolfarini, C.; Kaufman, M.J.
Abstract: A series of Al-rich Al-Mn-Ce alloys have been chill cast in copper molds and some were subjected to subsequent heat treatments. For all compositions studied, the ternary Al20Mn2Ce phase is formed as the primary phase surrounded by different constituents. The mechanical properties as a function of composition and heat treatment are presented and illustrate that this system is very versatile and that it is possible to tailor the compositions to produce alloys with high yield strengths, alloys with high hardnesses (for wear applications), and alloys with reasonably high ductilities. Alloys with high yield strengths and some ductility are obtained when the microstructure contains the ternary phase surrounded by the Al-Al11Ce3 eutectic constituent. Alloys with high hardnesses, can be obtained at higher Mn levels where the ternary phase and other intermetallics constitute most of the structure. Alloys with relatively high ductilities are possible at lower Ce and Mn levels where a metastable FCC solid solution of Mn in Al forms surrounding the ternary phase. Although the finely-distributed ternary phase is metastable, it appears to be relatively resistant to coarsening or decomposition. Finally, it is shown that Ce can be substituted by Mischmetal with no significant changes in either microstructure or properties. Graphical abstract: Highlights: The AlMnCe system is versatile, samples with very diverse properties were produced. In all samples produced, the Al20 Mn2 Ce intermetallic phase was formed primarily. The Al20 Mn2 Ce phase showed a good thermal resistance to coarsening and decomposition. Al-6Mn-4Ce sample displayed compressive yield strength superior to 750 MPa.